ESTUDO COMPARATIVO DA COMPETITIVIDADE DAS EMPRESAS DE MÁQUINAS FERRAMENTAS BRASILEIRAS: ANÁLISE MULTICRITÉRIOS - Sanches, João Carlos Santiago (2007)
The aim of the current study was to investigate through a comparative study, a competitive positioning of three Multitask and Tooling Machines in Brazilian market..Initial hypothesis were based on: a) the national tooling machine industries are being penalized with the industrial policies practiced by the federal government, and b) the relative importance attributed to multicriteria elements of the specifications of the national machines, when considered on the growing trends, are not always met by the imported competing machines as a result of aggregated technological values meant to reach plain competitiveness. Thus, we inquire: to what extent are the multitask and tooling machines selected for test are alighned with the chosen criteria and their relative importance appreciated by the two users of the machines. As a methodology the study adopted a multi-case study of two medium industries of the same sector. We used the multicriteria decision method through Analytic Hierarchy Process (AHP) so as to obtain the most suitable alternative between the national and imported multitasks similar machineries. Results indicate that for the two cases analyzed, it is advantageous to acquire the imported machines, even though it is notorious to mention the national technological advancement. These machines need innovations as they loose competitiveness, not to mention some important criteria such as versatility and productivity. Based on our findings therefore, we conclude that the national tooling and machines suppliers of the multitasks types analyzed in this study are not competitive as compared to the imported ones.